Book review: C. V. Ranganathan and Sanjeev Kumar (Eds), China and the Eurasian Region: Geographic and Geopolitical Influences. (June 2019) - Singh, Prashant Kumar
C. V. Ranganathan and Sanjeev Kumar (Eds), China and the Eurasian Region: Geographic and Geopolitical Influences . New Delhi: ICWA, 2018, pp. i–xxii + 1–301, ₹995. ISBN: 978-93-83445-31-8.